Audio-Visual Media as an Instructional Innovation to Increase Learning Interest in Indonesian Language - Sajma Sajma; Herlina Herlina; Sisriawan Lapasere; Zulnuraini Zulnuraini; Kasmawati Kasmawati (Papanda Publisher, 2026)
Low student learning interest remains a persistent challenge in Indonesian language instruction at the elementary level, often resulting from overreliance on lecture-based delivery and inadequate use of engaging instructional media. This study employed a two-cycle Classroom Action Research (CAR) design to examine the effectiveness of audio-visual media in increasing the learning interest of 28 fifth-grade students at SD Inpres 2 Besusu, Palu. Data were collected using a validated Likert-scale learning interest questionnaire (Cronbach's α = 0.81), teacher and student activity observation sheets, and documentation. Quantitative data were analyzed by calculating percentage scores against established category criteria, while qualitative data were processed through reduction, display, and conclusion-drawing stages. In Cycle I, the mean learning interest reached 61.86% (fair–good category), with only 14.29% of students achieving the very good level. Following reflective refinements to media content and teacher facilitation strategies, Cycle II yielded a mean of 83.09% (very good category), with 85.71% of students reaching the highest category—a 21.23 percentage-point increase. These findings demonstrate that iteratively designed audio-visual media, supported by facilitative teaching, effectively transforms passive learning behavior into active engagement in Indonesian language classrooms. This study contributes process-oriented evidence for the role of multimedia learning principles in elementary literacy education and offers a replicable intervention model for teachers seeking to increase student learning interest.